SELF-CARE ACTIVITIES AS PREDICTORS OF GOOD GLYCAEMIC CONTROL IN DIABETES: DIFFERENCES BETWEEN TYPE 1 AND TYPE 2 DIABETES - Karaman, Mina (Acta medicae Medianae, 2024)
Diabetes mellitus is a chronic disease that is mostly controlled by the affected individual nowadays. Activities in self-control of diabetes include self-monitoring of blood glucose, eating a healthy diet, being physically active, taking the recommended medication, and consulting health care professionals. Different studies have shown that educational and psychosocial interventions can have a significant effect on improving diabetes self-control and reducing complications. The aim of this study was to examine the differences in self-care activities between patients with Type 1 and Type 2 diabetes as well as the role of these activities in predicting good glycaemic control. Our results suggest that in Serbia people with Type 1 diabetes have a much harder task in achieving good glycaemic control than people with Type 2 diabetes, even when there is no difference between these groups in practicing the majority of self-care activities. In future, education for people with Type 1 diabetes should emphasise monitoring blood glucose. For both types of diabetes, a healthy diet should be addressed.